Stylometric analysis of Lafond's letter that never Wrote Simón Bolívar to San Martín - Raúl Isea (Journal of Current Scientific Research, 2023)
The goal is to analyze that Lafond’s letter by stylometric methods, supposedly written by Simón Bolívar to General San Martín about the destiny of Ecuador. The Delta function was calculated after evaluating 16 letters from Simón Bolívar and including another 11 letters from San Martín. The reason for including San Martín’s letter was to verify if the method used could distinguish between the two authors. A linguistic corpus was constructed using functional words, and a dendrogram was used to visualize the result. Finally, it is concluded that the letter to Lafond is false. Simón Bolívar never wrote this letter.
Keywords: Stylometric